Structural, microstructural, and transport properties of highly oriented LaNiO3 thin films deposited on SrTiO3(100) single crystal - Mambrini, G. P.; Leite, E. R.; Escote, M. T.; Chiquito, A. J.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Jardim, R. F. (American Institute of Physics (AIP), 2007)
Electrical conductive textured LaNiO3/SrTiO3 (100) thin films were successfully produced by the polymeric precursor method. A comparison between features of these films of LaNiO3 (LNO) when heat treated in a conventional furnace (CF) and in a domestic microwave (MW) oven is presented. The x-ray diffraction data indicated good crystallinity and a structural orientation along the (h00) direction for both films. The surface images obtained by atomic force microscopy revealed similar roughness values, whereas films LNO-MW present slightly smaller average grain size (similar to 80 nm) than those observed for LNO-CF (60-150 nm). These grain size values were in good agreement with those evaluated from the x-ray data. The transport properties have been studied by temperature dependence of the electrical resistivity rho(T) which revealed for both films a metallic behavior in the entire temperature range studied. The behavior of rho(T) was investigated, allowing to a discussion of the transport mechanisms in these films. (C) 2007 American Institute of Physics.